Structural evolution of poly(l-lactide) block upon heating of the glassy ABA triblock copolymers containing poly(l-lactide) A blocks. (22nd November 2016) - Nagarajan, S.; Deepthi, Krishnan; Gowd, E. Bhoje
Abstract: Two triblock ABA copolymers poly(l -lactide- b -dimethylsiloxane- b -l -lactide) (PLLA- b -PDMS- b -PLLA) and poly(l -lactide- b -ethylene glycol- b -l -lactide) (PLLA- b -PEG- b -PLLA) containing poly(l -lactide) were synthesized by ring opening polymerization ofl -lactide using bis(hydroxyalkyl) terminated PDMS and hydroxyl end-capped polyethylene glycol as macroinitiators, respectively. Both the triblock copolymers were melt-quenched to −40 °C to prepare the amorphous samples. The melt morphology of the triblock copolymers was preserved upon cooling the melt to −40 °C. PLLA and PDMS blocks are immiscible in the melt, and the amorphous triblock copolymer shows two distinct glass transition temperatures ( T g ) on heating. On the other hand, PLLA and PEG segments are miscible and the triblock copolymer shows the single T g . Structural evolution of PLLA during heating of the amorphous ABA triblock copolymers has been investigated by measuring the variable temperature small-angle and wide-angle X-ray scattering (SAXS and WAXS) and FTIR spectra. In the case of PLLA- b -PDMS- b -PLLA triblock copolymer (immiscible system), the mesophase of PLLA was found to appear just above the T g of PLLA block (∼45 °C), and on further heating the mesophase changed to the regular α form at around 90 °C. On the other hand, in PLLA- b -PEG- b -PLLA (miscible system), the mesophase of PLLA was found to appear at lower temperature i.e. −20 °C, because of the enhanced molecular mobility of PLLA chains in the presence of PEG. However, irrespective of the mesophase formation temperature, the ordered α form has appeared at around 90 °C. In this way, during heating of the amorphous triblock copolymers, the PLLA block was found to crystallize into the ordered α form always through the mesophase just above the T g of PLLA. These results are helpful in understanding the regularization process of semicrystalline polymers in different environments. Graphical abstract: Highlights: Structural evolution of poly(ʟ-lactide) blocks in miscible/immiscible block copolymers has been studied. Upon heating, the amorphous PLLA domains transiently transforms to the mesophase before transforming into the stable a form. The segmental mobility ( T g ) of the PLLA block controls the formation of mesophase PLLA in block copolymers. The miscible triblock copolymer favors the mesophase of PLLA at lower temperatures due to the enhanced molecular mobility.